Constitutional Treatment versus Clinical Homeopathy - Abermann, Christoph (Homœopathic Links, 2017)
Constitutional treatment by the Kent method is quite often not successful where severe diseases are involved. In such cases, it is better, when looking for a homoeopathic remedy, to go by the pathology of the disease and its accompanying symptoms. A detailed list of the other situations is provided —apart from severe pathologies—where what is called clinical prescription is beneficial. As a homoeopath, one has to have two tool kits: one for constitutional prescription and one for clinical prescription. The numerous differences between the two methods with regards to choice of remedy and potency, the repetition of the remedy and case management are illustrated in a table.
Keywords: Constitutional treatment; Kentianism; Clinical treatment; One-sided illness; Severer dissimilar illnesses; Homeopathic treatment; Case management; Repetition of remedy